Compressive strength of a glass ionomer cement under the influence of varnish protection and dietary fluids = Resistencia a la compresión de un cemento de ionómero de vidrio bajo la influencia de la protección del barniz y diversos productos alimenticios - Bohner, Lauren Oliveira Lima
The objective of this study was to evaluate the compressive strength of a glass ionomer cement (GIC) under the influence of varnish protection and dietary fluids. Eighty cylindrical test specimens were made from GIC and distributed into four groups (G1, G2, G3, G4) according to the dietary fluid. Each group was further divided into subgroups A and B according to the presence or absence of varnish protection. The eight subgroup samples were stored in distilled water for 30 days and received the following treatments for 14 days: G2A: varnish protection and immersion in soft drink, G2B: no varnish protection and immersion in soft drink, G3A: varnish protection and immersion in orange juice, G3B: no varnish protection and immersion in orange juice, G4A: varnish protection and immersion in yogurt, G4B: no varnish protection and immersion in yogurt. The immersion procedure was performed three times a day, for 15 minutes at a time, for a total of 14 days. The samples from subgroups G1A (with varnish) and G1B (without varnish) were used as controls and stored in distilled water only for 30 days. The samples were submitted to a compressive strength test after the immersion period. The results were analyzed using the ANOVA 2, Tukey test (5%) and Student's t-test (5%). There were no significant differences between the subgroups, except for the subgroup with varnish protection and immersion in orange juice, which showed reduced GIC compressive strength.